Case report: Changes in defense mechanisms, personality functioning, and body mass index during psychotherapy with patients with anorexia nervosa - Conversano, Ciro; Di Giuseppe, Mariagrazia; Lingiardi, Vittorio (Frontiers in Psychology, 2023)
Eating disorders (EDs) are difficult to treat in psychotherapy due to their pervasive symptomatology and frequent and rapid relapses. Restrictive Anorexia Nervosa (AN) is the most challenging ED, often associated with severe physical and mental conditions. Perceived as an ego-syntonic syndrome that somehow protect the patient from a number of developmental tasks, treating AN requires extensive multidisciplinary long-term intervention. As other emotion regulation strategies, defense mechanisms mediate individual’s reaction to internal or external stressors, including those related to ED conditions. Improving defensive functioning adaptiveness predict psychotherapy outcome and are an essential component of therapeutic process. In this study we qualitatively described changes in the use of defense mechanisms, personality functioning (PF) and body mass index (BMI) in two patients with severe AN in treatment with intense dynamic psychotherapy. Changes in personality functioning and defense mechanisms were periodically assessed every 6 months using clinician-report measures as the Shedler-Westen Assessment Procedure-200 (SWAP-200) and the Defense Mechanisms Rating Scales Q-sort (DMRS-Q), respectively. BMI was also monitored throughout the treatment. Qualitative description of patient’s defensive profile and quantitative score on all range of defense mechanisms were used for studying changes in patients’ use of defenses during the treatment and relationships between defenses and outcome indexes. Personality and defensive functioning improved after one year of intense dynamic psychotherapy, independently from BMI improvement. All outcome indexes dramatically decreased before a scheduled interruption of the treatment underling that an integrated therapeutic approach in essential for improving and eventually orienting towards the complete ED symptoms remission. Long-term dynamic psychotherapy fosters self-awareness of psychological distress and enhances more mature ways of coping. Monitoring changes in personality and defense mechanisms helps in understanding patient’s reactions to stressful life events and in developing specific therapeutic interventions.